2019
DOI: 10.1590/s1677-5538.ibju.2018.0574
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis prior to urodynamic study in patients with traumatic spinal cord injury. Is there an indication?

Abstract: Study design: Retrospective cohort of patients with traumatic spinal cord injury (SCI) that have been hospitalized for physical-functional rehabilitation purposes. Objectives: To compare the incidence of urinary tract infection (UTI) after urodynamic study (UDS) in three hospitals that adopted different protocols with regard to the preparation of patients. Setting: Sarah Network of Rehabilitation Hospitals, Brazil. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Although there is no consensus regarding the use of prophylactic antibiotics before UDS, it is recommended that prophylactic antibiotics should be used before all invasive procedures, including UDS in high-risk groups for UTI, similar to patients with SCI [9,[18][19][20][21][22]. Conversely, a retrospective study of 661 patients with SCI [23] showed no significant difference in the incidence of post-UDS UTI between groups using and not using prophylactic antibiotics, and concluded that prophylactic antibiotics should not be used. Although an exact comparison is lim-ited by the study design, the incidence of post-UDS UTI in our study (1.5%) was markedly lower than that in other studies (9.7%-15.8%) [6,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus regarding the use of prophylactic antibiotics before UDS, it is recommended that prophylactic antibiotics should be used before all invasive procedures, including UDS in high-risk groups for UTI, similar to patients with SCI [9,[18][19][20][21][22]. Conversely, a retrospective study of 661 patients with SCI [23] showed no significant difference in the incidence of post-UDS UTI between groups using and not using prophylactic antibiotics, and concluded that prophylactic antibiotics should not be used. Although an exact comparison is lim-ited by the study design, the incidence of post-UDS UTI in our study (1.5%) was markedly lower than that in other studies (9.7%-15.8%) [6,16].…”
Section: Discussionmentioning
confidence: 99%
“…The authors are to be commended on this study, which further adds to the limited literature available on urodynamic findings in central cord syndrome. They do not state if antimicrobial prophylaxis was administered pre urodynamic evaluation, which has recently been debated, 2 or if any patient developed dysreflexia.…”
mentioning
confidence: 99%
“…We read with interest the recent paper by da Silva et al examining effects of antibiotic prophylaxis and risk of urinary tract infection for spinal cord injured patients undergoing urodynamic studies. The authors describe a multi institutional study involving 661 patients who underwent urodynamic evaluation over 2 years ( 1 ). Three different antibiotic protocols are described in separate institutions and a cumulative infection rate of 3.18% was found.…”
mentioning
confidence: 99%
“…No differences between patient age or ASIA classification were found to have an association with the development of subsequent urinary tract infection. However, patients with injuries at T6 or above were at increased risk of developing urinary tract infection following urodynamic evaluation ( 1 ).…”
mentioning
confidence: 99%